Design of Ultra Large Normal Dispersion ZBLAN Photonic Crystal Fiber and Its Application in Mid-IR Ultra Short Fiber Lasers - Ying Gao; Jian-feng Li; Ya-zhou Wang; Yi-Wen Shi; Fei Liu; Kun Li; Jian Yang; Yong Liu (IEEE Photonics Journal, 2018)
A ZBLAN photonic crystal fiber (PCF) with normal dispersion is theoretically designed and investigated. The designed PCF can provide a large normal dispersion coefficient and a low confinement loss in a broad wavelength range of 1.8–3.6 μm. Especially, the PCF exhibits an ultra large normal dispersion value of −351.3 ps/km/nm and a small confinement loss of 0.05 dB/m at 2.9 μ m. By using the designed PCF as a dispersion compensator in a mode-locked ZBLAN fiber laser, stretched pulse with compressed pulse duration of 1.56 ps is numerically achieved.